Beyond Dynamic Drawings: Restoring and Reusing Interactive 3D Visualizations in a Humanities Context (Research Data Journal for the Humanities and Social Sciences, 2024)
In recent years, interest in three-dimensional visualizations as a complement to traditional text-based humanities scholarship has surged. These visualizations allow for new analysis methods and may serve as an interpretative tool, potentially leading to new insights for creators and viewers. However, contrary to more traditional publications, a myriad of preservation issues occurs from the moment a 3D visualization is created. This data paper illustrates the complexity of preserving 3D visualizations in a humanities context using six interactive visualizations produced in research data journal for the humanities and social sciences 9 (2024) 1–17 the Dynamic Drawings in Enhanced Publications project (2013). The visualizations serve as a concrete case study for the restoration, preservation and renewed publication of 3D content. This data paper sketches the general preservation challenges that led to non-functional interactive visualizations. The authors detail the process of restoring the visualizations from the original data and opening them up for potential reuse. To underline reuse possibilities, the authors provide tentative examples for VR and AR platforms. After presenting the dataset, they discuss the implications of the restoration process for future preservation practices of unstable interactive content. The authors introduce a ‘composite elements approach’, combining visual and non-visual levels of documentation necessary for the maintenance of interactive visualizations.